Effects of the ratio of silane to 10-methacryloyloxydecyl dihydrogenphosphate (MDP) in primer on bonding performance of silica-based and zirconia ceramics. (December 2020) - Koko, Minkhant; Takagaki, Tomohiro; Abdou, Ahmed; Inokoshi, Masanao; Ikeda, Masaomi; Wada, Takahiro; Uo, Motohiro; Nikaido, Toru; Tagami, Junji
Abstract: Objectives: The purpose of the study was to evaluate the effects of the ratio of different concentrations of silane to 1 wt% 10-methacryloyloxydecyl dihydrogenphosphate (MDP) in primer on the performance and durability of bonding to silica-based and zirconia ceramics. Methods: Phosphoric acid–treated lithium–disilicate (LD) and alumina-blasted zirconia specimens were assigned to five groups according to surface chemical treatment with different concentrations of γ-methacryloxypropyltrimethoxysilane (γ-MPTS) to 1 wt% MDP containing primer as follows: S0) without γ-MPTS; S1) 1 wt% γ-MPTS; S2) 2 wt% γ-MPTS; S5) 5 wt% γ-MPTS and S10) 10 wt% γ-MPTS. After priming, stainless-steel rods were bonded to the specimens with PanaviaV5 cement. Tensile bond strength (TBS) test was evaluated after 24-h (TC0) or 5000 thermocycling (TC5K). The wettability of primer-treated surfaces was measured using contact angle measurements. Surface elemental composition of zirconia was determined with X-ray photoelectron spectroscopy (XPS). The TBS data were analyzed using Weibull analysis. Contact angle data were analyzed by three-way analysis of variance (α = 0.05). Results: Before thermocycling, S5 (34.3 ± 4.5 MPa) showed the highest TBS compared to S1 (27.8 ± 5.2 MPa) and S2 (29.7 ± 4.8 MPa), and insignificant difference with S10 (30.6 ± 6.2 MPa) in LD. For zirconia there was no significant difference in all silane containing primers with S0 ( p  > 0.05). Thermocycling decreased TBS for all experimental groups among both ceramics ( p  < 0.05). Contact angles increased in S5 and S10 for both LD and zirconia ceramics. XPS analysis revealed that phosphorous peak of MDP was detected after priming. Additionally, silica peak of γ-MPTS coexist with MDP in S5 on zirconia surface. Significance: The bond strength of lithium-disilicate ceramics was improved with 5% γ-MPTS in MDP primer. Moreover, increasing percentage of γ-MPTS by more than 5% has not improved the bond strength, conversely, it can alter the long-term durability of the bonded ceramic. MDP primers alone are best suited for efficient bonding of resin cement with zirconia ceramic. Graphical abstract: Image 1 Highlights: Experimental primers can influence the bond strength and durability. The effective silane-MDP ratio was ceramic materials–dependent. Thermocycling decreased the tensile bond strength of all experimental primers.